ACTR-18. A PHASE IB/II CLINICAL TRIAL OF DODECAFLUOROPENTANE EMULSION (DDFPE) AS A RADIOSENSITIZER IN GLIOBLASTOMA. (11th November 2019) - Lickliter, Jason; Ruben, Jeremy; Jennens, Ross; Kichenadasse, Ganessan; Gzell, Cecelia; Mason, Ralph; Carmody, Raymond; Becker, Jennifer; Stea, Baldassarre; Zhou, Heling; Sellenger, Michael; Longacre, Olivia; et al.
Abstract: BACKGROUND: Tumor hypoxia decreases the response of glioblastoma multiforme (GBM) to radiotherapy (RT) and chemotherapy (temozolomide[TMZ]). The purpose of this study was to evaluate the safety and efficacy of a novel oxygen therapeutic, dodecafluoropentane emulsion (DDFPe), in chemoradiation treatment of GBM and stratify the results based on predicted TMZ response. METHODS: With ethics approval and informed consent, 11 adult GBM patients were enrolled. Patients were administered DDFPe via IV infusion (2% w/vol at doses of 0.05, 0.1 or 0.17 mL/kg) within 5–30 minutes prior to each 2 Gy fraction of RT (30 fractions over 6-weeks) while breathing supplemental oxygen. Patients also received standard concurrent and adjuvant TMZ. To evaluate the reversal of tumor hypoxia, patients underwent oxygen-sensitive (TOLD) MRI before and after DDFPe administration. Patients were also studied with serial MRI scans per standard of care and followed for survival. RESULTS: The non-serious adverse events considered by the investigator to be possibly, probably, or definitely related to DDFPe administration included fatigue (n=4), headache (n=2) and decrease in platelet count (n=2). Serious adverse events included two patients with symptomatic radiation necrosis: one patient at each of dose levels 0.1 and 0.17 mL/kg. Enrollment continued at the 0.1 mL/kg dose without additional significant DDFPe-related toxicity. Historically, the average overall survival for GBM patients is about 14.6 months. The median overall survival for the study was 591 days, or 19.4 months. According to independent review of the serial MR images, the median time to progression was 555 days, or 18 months, compared to a historical control of 6.9 months. TOLD MRI showed a trend in improved tumor oxygenation. CONCLUSION: Although small, this trial shows that DDFPe used as a radiosensitizer appears to be safe and may provide some survival benefit. The FDA has allowed a Phase II clinical trial to assess its effectiveness.